Benefits and risks of collaboration between watchdogs: the Western Australian experience - Wilkins, Peter; Phillimore, John; Gilchrist, David (Routledge, 2017)
There has been little discussion or analysis regarding how integrity agencies work together. This paper looks at Western Australian watchdog collaboration activities in the context of concerns raised by senior judicial and political figures. Issues addressed include whether such collaborative activities impinge on the independence of watchdogs, impede their ability to oversight each other, and whether such activities take them beyond their legislative remit. Analysis of practice revealed a wide array of collaboration activities of varying intensity. It was found that such collaboration enhanced watchdog effectiveness while the concerns expressed appeared over-stated. The analysis identified precautions required to protect watchdog independence and ensure accountability for collaborative activities, including steps to recognize and remove barriers to greater collaboration.